ANALYZING PATTERNS OF CLASSROOM INTERACTION : A Case Study in an EFL Class of a Senior High School in Bandung - Nugraha, Ade Purna (2015)
This study attempts to reveal the patterns of classroom interaction that appear during the processes of teaching and learning. Previous studies on classroom interaction found that classroom interaction plays an important role in determining the success of students' learning and that classroom interaction consists of several patterns. These patterns of classroom interaction are varied which mostly depend on teachers' belief toward the classroom itself. The present study tried to investigate the patterns of classroom interaction and to gain students' responses toward the processes of teaching and learning conducted by the teacher. The study was conducted in a senior high school in Bandung involving one class of first graders and one classroom teacher as participants. It employed a qualitative study in the perspective of the pedagogical microscope in systemiotic approach to reveal and to analyze the patterns of classroom interaction during the processes of teaching and learning. In order to obtain the necessary data the study used video recording, classroom observation and guided interview as instruments. The data which was analyzed by using pedagogical microscope was the transcription of the video recording. The study found that in general the classroom interaction is interactive. It was revealed that the dominance of knowledge exchanges (50%) and skill exchanges (35%) during the process indicated that the classroom was focused into knowledge transfer as well as knowledge practice. It means that teacher transferred the knowledge to students in order to enable them to practice the knowledge and their English skill. It can be seen from the main activity which was designed by the teacher for the students to actively practice their English skill in describing people's physical appearances. From the result of the interview, it was found that students responded positively toward the teaching and learning process conducted by the teacher. Most students found the classroom activities, especially the "Eat Bulaga" game, interesting so that they were motivated to learn in the classroom. Most of them argued that the game was already familiar to them as they used to watch the show about the game on TV. Based on the findings, it is recommended that further analysis by using pedagogical microscope as a research instrument be used, as the instrument could reveal interactions' patterns as well as evaluates the teaching and learning process in getting further improvement in the innovation of teaching and learning process. Penelitian ini bertujuan untuk mengungkap pola -pola interaksi yang terjadi selama proses belajar mengajar. Penelitian-penelitian terdahulu pada interaksi kelas menemukan bahwa interaksi kelas berperan penting dalam menentukan kesuksesan belajar siswa dan interaksi kelas juga terdri dari beberapa pola. Pola-pola interaksi kelas ini berbeda tergantung dari keyakinan guru terhadap kelas itu sendiri. Penelitioan ini mencoba menemukan pola interaksi kelas dan memperoleh respon-respon siswa terhadap proses belajar-mengajar di kelas tersebut. Penelitian ini dilakukan di sebuah sekolah menegah atas di Bandung dan melibatkan satu kelas satu dan seorang guru sebagai objek penelitian. Penelitian ini menggunakan pendekatan kualitatif dalam perspektif mikroskop pedagogi dalam pendekatan sistemiotik untuk mengungkap dan menganalisa pola-pola interaksi selama proses belajar-mengajar. Untuk memperoleh data, penelitian ini menggunakan rekaman video, observasi kelas, dan interview sebagai instrumen. Data yang dianalisis menggunakan mikroskop pedagogi adalah data dari transkrip rekaman video. Penelitian ini menemukan bahwa pada umumnya interaksi yang terjadi dikelas sudah aktif dan interaktif. Hal ini dibuktikan oleh dominasi dari pola knowledge exchanges (50%) dan skill exchanges (35%) selama proses belajar-mengajar yang mengindikasikan bahwa kelas tersebut berfokus pada teransfer ilmu dan latihan berbahasa Inggris untuk siswa. Hal itu menunjukkan bahwa guru mentransfer ilmu untuk membuat siswa bias mempraktekkan dan melatih kemampuan berbahasa inggris mereka dalam mendeskripsikan penampilan fisik seseorang. Dari hasil wawancara ditemukan bahwa sebagian besar siswa memberikan respon positif terhadap proses belajar-mengajar yang diselenggarakan guru dikelas. Sebagian besar siswa berpendapat bahwa permainan Eat Bulaga menarik dan membuat mereka termotivasi untuk belajar bahasa inggris. Mereka sudah familiar dengan game tersebut karena mereka sering menonton acaranya di TV. Berdasarkan hasil temuan dalam penelitian ini, penelitian-penelitian selanjutnya yang menggunakan pendekatan mikroskop pedagogik sebagai instrumen sangat dianjurkan untuk mengungkap pola-pola interaksi kelas sehingga perbaikan proses belajar-mengajar dapat tercapai.